2021
DOI: 10.1177/23259671211002482
|View full text |Cite
|
Sign up to set email alerts
|

Repair Integrity and Functional Outcomes Between Knot-Tying and Knotless Suture-Bridge Arthroscopic Rotator Cuff Repair: A Prospective Randomized Clinical Trial

Abstract: Background: Knot-tying suture-bridge (SB) rotator cuff repair may compromise the vascularity of the repaired tendon, causing tendon strangulation and medial repair failure. The knotless SB repair technique has been proposed to overcome this possibility and decrease retear rates. Purpose: To compare clinical and structural outcomes and retear patterns between the knot-tying and knotless SB techniques. We hypothesized that the knotless technique would result in lower retear rates owing to the preservation of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…The 12 articles included a total of 1411 shoulders, with tear sizes being medium in 4 studies, 12 , 13 , 16 , 22 medium to large in 3 studies, 9 , 28 , 29 small to massive in 2 studies, 10 , 23 and not reported in 3 studies. 3 , 11 , 19 One study 23 was categorized as having level 1 evidence, 3 studies 3 , 13 , 22 had level 2 evidence, and 8 studies 9 12 , 16 , 19 , 28 , 29 had level 3 evidence. The studies had a MINORS score ranging from 15 to 19, indicating that the methodology was fair to good.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 12 articles included a total of 1411 shoulders, with tear sizes being medium in 4 studies, 12 , 13 , 16 , 22 medium to large in 3 studies, 9 , 28 , 29 small to massive in 2 studies, 10 , 23 and not reported in 3 studies. 3 , 11 , 19 One study 23 was categorized as having level 1 evidence, 3 studies 3 , 13 , 22 had level 2 evidence, and 8 studies 9 12 , 16 , 19 , 28 , 29 had level 3 evidence. The studies had a MINORS score ranging from 15 to 19, indicating that the methodology was fair to good.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies 3 , 9 13 , 16 , 19 , 22 , 23 , 28 reported the overall retear rate of both knot-tying and knotless techniques. The overall retear rates of the knot-tying and knotless group were 20.1% and 20.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated lower risk of type 2 repair failures with using knotless techniques has been thought to be advantageous. 9 A recent meta-analysis similarly found no difference in clinical outcomes between knot-tying and knotless double-row arthroscopic RCR, as well as comparable retear rates between techniques. One study included in the analysis found a significantly lower retear rate in the knotless group.…”
Section: Discussionmentioning
confidence: 95%
“…In a prospective randomized controlled trial, Sahin et al. 9 found that the standard knot-tying and the knotless technique during suture-bridge rotator cuff repair both resulted in significant improvement of clinical outcomes at mid-term follow-up, including comparable postoperative range of motion, pain, and functional outcomes. Both techniques also had similar retear rates; however, retear pattern differed significantly, with the knot-tying technique resulting in significantly greater type 2 (medial) retears, while the knotless technique was associated with greater type 1 (lateral) retears.…”
Section: Discussionmentioning
confidence: 99%